The Patient's Family Experience Accompanying Patients In The Intensive Care Unit (ICU) Of Imelda Pekerja Indonesia General Hospital - Manurung, Nixson; Hondro, Ododo (Sean Institute, 2024)
Critical patients are patients who experience critical pain due to physiological, psychosocial, developmental, and spiritual changes. Patients who suffer from critical illness will experience hospitalization that requires the role of the family as a family support system. The role of the family in dealing with critical patients can have physical impacts, such as fatigue, sleep disturbances, and health problems. Psychological impacts such as anxiety, fear, sadness and depression and social impacts in the form of reduced communication and social isolation. The purpose of this study is to find out the patient's family experience while accompanying the patient in the ICU room of the Imelda Pekerja Indonesia General Hospital. This study uses a qualitative type of research with a phenomenological approach. The sample in this study consisted of 6 participants with nuclear family inclusion criteria, over 18 years old who had waited for more than 3 days in the ICU Room. Data collection techniques with in-depth interviews. The results of this study obtained 4 themes that describe this family experience, namely fear of not being able to see patients again, pity to see patients with many tools, abandoning the routine of seeing patients, and relying on God. Further research suggestions should provide interventions related to the impact that arises when families face critical patients.